Recovery from resistance exercise in older adults: a protocol for a scoping review. Issue 1 (31st January 2022) - Hayes, Eleanor Jayne; Stevenson, Emma; Sayer, Avan Aihie; Granic, Antoneta; Hurst, Christopher
Abstract : Introduction: Resistance exercise has been shown to improve muscle health in older adults and is recommended as a front-line treatment for many health conditions, including sarcopenia and frailty. However, despite considerable research detailing the potential benefits of resistance exercise programmes, little is known about how older adults recover from individual exercise sessions. This scoping review will examine the current evidence surrounding the acute post-exercise effects of resistance exercise and the exercise recovery process in older adults to inform future research and exercise prescription guidelines for older adults. Methods and analysis: The methodological framework of Arksey and O'Malley (2005) will be applied for this scoping review. A systematic search of five online databases and the hand-searching of reference lists of identified articles will be used to identify relevant papers. Studies that aim to measure exercise-induced muscle damage or exercise recovery following a resistance exercise session in participants aged 65 years and over will be included. Qualitative and quantitative data from relevant studies will be presented in a tabular format. Results will be summarised in narrative format. Key findings will be discussed concerning resistance exercise prescription in older adults. Dissemination: This review will be used to direct further research surrounding the exercise recovery process from resistance exercise in older adults and will also aid in designing specific exercise prescription guidelines for an older population. Findings will be relevant to researchers, clinicians, health workers and policy-makers and disseminated through publications and presentations.